2020
DOI: 10.1016/j.celrep.2020.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Limits Endothelial Cell Extrusion in the Zebrafish Dorsal Aorta

Abstract: Highlights d Endothelial cell (EC) nuclei are enriched in the ventral dorsal aorta (DA) during EC movement d DA wall deforms asymmetrically in response to pulsatile blood flow d Low blood flow or abnormal mechanosensing results in increased cell extrusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 70 publications
5
26
0
Order By: Relevance
“…However, our results indicate that without a strong intracellular cytoskeletal network regulated by Snai1, the heartbeat-induced mechanical forces can lead to an increase in cell extrusion. While it has been shown that an increase in cell contractility due to changes in morphology, adhesion or cell density drives cell extrusion 23,24,26,28,29,52,53 , we present evidence that external mechanical forces contribute to non-apoptotic CM extrusion during cardiac development, and that actomyosin and IF cytoskeletal regulation is critical to prevent CM extrusion.…”
Section: Desmin B Overexpression In Cms Promotes Their Extrusionmentioning
confidence: 50%
“…However, our results indicate that without a strong intracellular cytoskeletal network regulated by Snai1, the heartbeat-induced mechanical forces can lead to an increase in cell extrusion. While it has been shown that an increase in cell contractility due to changes in morphology, adhesion or cell density drives cell extrusion 23,24,26,28,29,52,53 , we present evidence that external mechanical forces contribute to non-apoptotic CM extrusion during cardiac development, and that actomyosin and IF cytoskeletal regulation is critical to prevent CM extrusion.…”
Section: Desmin B Overexpression In Cms Promotes Their Extrusionmentioning
confidence: 50%
“…In addition, the contribution of different flow-derived forces (e.g., shear stress and circumferential stretch) to specific EC behaviors involved in vascular morphogenesis still needs to be clarified. These open questions are difficult and will benefit from a number of new tools: optogenetics (Chow and Vermot, 2017;Krueger et al, 2019), functionalized protein binders (Bieli et al, 2016), three dimensional live-imaging and processing (Campinho et al, 2020;Prahst et al, 2020) as well as tissue engineering approaches where forces are trackable and accurately controlled (Duchemin et al, 2019b;Vianello and Lutolf, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that force has also been shown to activate mechanosensitive ion channels [3,65]. In a zebrafish model analyzing the impact of blood flow on endothelial cell extrusion, the mechanosensitive cationic channel polycystic kidney disease 2 (pkd2) was found to be responsible for modulating endothelial cell extrusion independent of primary cilia [65]. This finding contrasts with other work that implicates primary cilia as mechanosensors in EHT [66].…”
mentioning
confidence: 82%
“…Cyclic strain in the hemogenic endothelium is necessary for HSPC maintenance, maturation, and proliferation via YAP1 signaling [103] 2020 Blood flow regulates endothelial cell extrusion in blood vessels [65] activation, which is important for downstream mechanotransduction signaling and cytoskeletal remodeling [51,53]. VEcadherin is a vital component of adherens junctions and plays a key role in maintaining vascular integrity [51,52,58].…”
mentioning
confidence: 99%
See 1 more Smart Citation